Glycaemic Control: A Balancing Act or A Different Approach? - Fava, Stephen (Current Diabetes Reviews, 2014)
The prevalence of diabetes is increasing world-wide. Tight glycaemic control has been shown to reduce diabetes complications in a number of landmark trials. Apart from increasing the risk of microvascular and macrovascular disease, poor glycaemic control is also associated with cognitive and memory impairment as well as with mood disturbance. However, tighter glycaemic control with conventional anti-hyperglycaemic medication is also associated with increased risk of hypoglycaemia. There is increasing evidence that hypoglycaemia is much more than a troublesome inconvenience. Indeed it is associated with acute cognitive impairment, dementia, increased risk of falls, rebound hyperglycaemia with consequent loss of glycaemic control, acute coronary syndrome and increased mortality. Hence, a very difficult balance needs to be achieved so as to achieve the best glycaemic control possible, whilst avoiding hypoglycaemia. This paper will briefly discuss the potential benefits of tight glycemic control and reviews the risks associated with hypoglycaemia. A paradigm shift in diabetes care may be needed; use of newer anti-hyperglycemic agents with low hypoglycaemia risk may allow us to achieve good control in most patients whilst avoiding the serious consequences of hypoglycaemia. This may be especially important in those at significant risk of hypoglycaemia (e.g. those with brittle diabetes) or of its consequences such as elderly patients, those in certain occupations or those with cardiovascular disease or epilepsy.
Keywords: glycaemic control